Dream's end - Kuttner, Henry, 1915-1958; Marchioni, M. (Marco Enrico), 1901-1987 (Salt Lake City, UT : Project Gutenberg, 2022)
"Dream's End" by Henry Kuttner is a science fiction novella published in the mid-20th century, specifically in the July issue of Startling Stories in 1947. The story revolves around the psychological and philosophical explorations of the human mind through the lens of psychiatry and emerging technology, particularly the idea of using an "empathy surrogate" to cure severe mental disorders. The plot centers on Dr. Robert Bruno, a psychiatrist who conducts a groundbreaking experiment to treat a manic-depressive patient, Gregson, by temporarily merging with his consciousness. As Bruno undertakes this risky venture, he grapples with the nature of reality and sanity, finding himself in a surreal dream-like state that challenges his perception of existence. As he witnesses bizarre transformations and experiences disorienting visions, he confronts deep-seated fears of losing control over his mind. The story builds tension as Bruno strives to ascertain whether he is truly awake or trapped in a hallucinatory spiral, ultimately revealing themes of individualism, the fragility of sanity, and the complexities of the human psyche. (This is an automatically generated summary.)
Release date is 2022-05-25
Greg Weeks, Mary Meehan, Alex White & the online Distributed Proofreaders Canada team at https://www.pgdpcanada.net
Keywords: Science fiction; Short stories; Physicians -- Fiction; Psychological fiction; Dreams -- Fiction; Experiments -- Fiction